Person-centered care for dementia patients (back-end system development) - Tan, Wen Kai (Nanyang Technological University, 2023)
Dementia is a general term that describes a group of disorders which impair cognitive functions like the ability to remember, think, or make decisions that interferes with doing everyday activities. Research has proven that there exist possibilities to reduce the declination of cognitive functions by providing person-centered care to the patients. Person-centered Care (PEAR) system was developed to help better coordinate healthcare services to the dementia patients. PEAR is available on both web and mobile platforms which makes it accessible for its users to access or manage patient’s information. It has been in development since 2017 and the focus of this project is to improve the project development workflow and the maintainability of the project. As part of the backend development team, software tools were set up for developers to iterate and test their Application Programming Interface (API) faster. To ensure longevity of the project, many man hours went into researching proper coding practice for the framework used and cleaning up the codebase. Existing APIs were improved in terms of being less prone to errors and fulfilling the requirements. New APIs were implemented based on the requirements of the frontend members. Automated test scripts were deployed to the continuous integration and continuous deployment pipeline so that the tests run whenever there are changes to the code in the repository.